Understanding the Relative Roles of Salmon Spawner Enrichment and Disturbance: A High-Frequency, Multi-Habitat Field and Modeling Approach - Janine Rüegg; Dominic T. Chaloner; Ford Ballantyne; Peter S. Levi; Chao Song; Jennifer L. Tank; Scott D. Tiegs; Gary A. Lamberti (Frontiers in Ecology and Evolution, 2020)
Organisms exert multiple, and often contrasting, influences on ecosystems. During their spawning runs, Pacific salmon (Oncorhynchus spp.) deliver nutrients to freshwater ecosystems, but also disturb benthic sediments during upstream migration and nest building. The relative importance of these contrasting roles is not well understood, especially in relation to the dynamics of other environmental drivers. To assess the influence of salmon-mediated enrichment and disturbance, we measured stream biofilm metrics (production, respiration, chlorophyll a [chla], ash-free dry mass, stable isotope signatures, ∼ every 8 days) and stream variables (spawner and carcass abundance, dissolved nutrients, temperature, discharge, light, daily to every few days) from July through September (salmon arrived in August), in multiple habitats of a southeast Alaska (USA) stream. Biofilm production and biomass increased around the start of the salmon run, but declined later in the run. Biofilm stable isotope composition indicated incorporation of salmon-derived carbon and nitrogen (N) during the latter part of the run. Biofilm biomass differed among benthic habitat types (i.e., riffles, pools, stream edges) but temporal patterns were generally similar, suggesting that salmon and environmental influences were not habitat-specific. We used these high-frequency field data to parameterize an ordinary differential equation model for dissolved inorganic N, chla, and cellular N, and estimated model parameters using Markov chain Monte Carlo. Posterior distributions indicated that (1) habitats and locations were generally similar in model parameters, (2) removing the effect of salmon resulted in no change in biofilm chla early in the run (mid-August), but higher chla biomass for some habitats later in the run (September), and (3) the overall integrated salmon effect over the run was one of biofilm loss. Only by combining high frequency biofilm and environmental data with a process-based model could we determine how environmental context dynamics interact with salmon run dynamics to modulate the biofilm response in natal spawning streams.